ACCOUN-TECH-CY: A Correlational Study of Technological Literacy and Academic Performance Among Accountancy Students in Pamantasan ng Lungsod ng San Pablo - Callo, Aeron Cedrick; Fideli, Carlos Miguel; Ibe, Rhegine Blaize; Padernilla, Glaiza Mae; Pagkaliwangan, Kristene (International Journal of Sustainability and Advanced Integrated Research, 2026)
The rapid advancement of digital technologies has significantly transformed accounting education, increasing the demand for strong technological literacy among students. This study examined the relationship between technological literacy and academic performance among accountancy students at Pamantasan ng Lungsod ng San Pablo. A quantitative correlational research design was employed, utilizing a validated researcher-made survey questionnaire administered to randomly selected respondents. Descriptive statistics were used to assess levels of technological literacy and academic performance, while Spearman Rank-Order Correlation determined the relationship between variables. Results revealed that students demonstrated high levels of basic digital skills but comparatively lower proficiency in accounting software. Academic performance was also rated high. Furthermore, findings indicated a significant positive relationship between technological literacy and academic performance. These results imply that increased technological competence contributes to better academic outcomes. The study highlights the importance of integrating technology-based instruction in accounting education and recommends strengthening curriculum interventions focused on specialized digital tools.